Respuesta :

Answer:

[tex]f^{-1}(x)=-3(+/-)\sqrt{\frac{10x+7}{2}}[/tex]

Step-by-step explanation:

we have

[tex]5y+4=(x+3)^{2}+\frac{1}{2}[/tex]

Exchange x for y and y for x

[tex]5x+4=(y+3)^{2}+\frac{1}{2}[/tex]

Isolate the variable y

[tex]5x+4-\frac{1}{2}=(y+3)^{2}[/tex]

[tex]5x+\frac{7}{2}=(y+3)^{2}[/tex]

[tex]\frac{10x+7}{2}=(y+3)^{2}[/tex]

Take square root both sides

[tex](y+3)=(+/-)\sqrt{\frac{10x+7}{2}}[/tex]

[tex]y=-3(+/-)\sqrt{\frac{10x+7}{2}}[/tex]

Let

[tex]f^{-1}(x)=y[/tex]

[tex]f^{-1}(x)=-3(+/-)\sqrt{\frac{10x+7}{2}}[/tex]